2008
DOI: 10.1007/s00268-008-9854-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rikkunshito, a Chinese Herbal Medicine, on Stasis in Patients After Pylorus‐Preserving Gastrectomy

Abstract: Rikkunshito improved gastric emptying and ameliorated postoperative symptoms of patients who had undergone a PPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 33 publications
1
35
0
2
Order By: Relevance
“…Rikkunshito relieved GERD-related symptoms, via its gastric emptying-enhancing actions, resulting in reducing the intraesophageal acid exposure time by improving clearance [9,22]. Other clinical studies of FD-like patients [23,24], cancer patients [25], and patients after surgery [26], have proven that rikkunshito reduced gastrointestinal tract symptoms by improving gastric emptying. Recently, rikkunshito was also shown to have increased the fasting level of plasma acyl-ghrelin, a peptide that is an orexigenic hormone associated with gastrointestinal tract motility, in healthy adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…Rikkunshito relieved GERD-related symptoms, via its gastric emptying-enhancing actions, resulting in reducing the intraesophageal acid exposure time by improving clearance [9,22]. Other clinical studies of FD-like patients [23,24], cancer patients [25], and patients after surgery [26], have proven that rikkunshito reduced gastrointestinal tract symptoms by improving gastric emptying. Recently, rikkunshito was also shown to have increased the fasting level of plasma acyl-ghrelin, a peptide that is an orexigenic hormone associated with gastrointestinal tract motility, in healthy adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…Rikkunshito is an orally administered Japanese herbal (Kampo) preparation that is widely prescribed for patients showing various gastrointestinal symptoms such as gastroesophageal reflux (5,6), dyspeptic symptoms of post gastrointestinal surgery (7,8), and chemotherapy-induced nausea (9). Rikkunshito is composed of 8 constituents: Glycyrrhizae radix (4.7%), Zingiberis rhizoma (2.3%), Atractylodis lanceae rhizoma (18.6%), Zizyphi fructus (9.3%), Aurantii nobilis pericarpium (9.3%), Ginseng radix (18.6%), Pinelliae tuber (18.6%), and Hoelen (18.6%).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was reported that, postoperatively, dyspeptic pediatric patients exhibited symptomatic relief and a significant reduction in the mean symptom score after treatment with rikkunshito over a 1-month period [21]. In the sphere of gastrointestinal surgery, rikkunshito improved gastric emptying and ameliorated the postoperative symptoms of patients who had undergone a pyloruspreserving gastrectomy (PPG) [22]. Although the attenuation of postoperative symptoms observed in these studies was reproduced in our present study, we failed to detect significant differences in the VAS scores or in any of the DAUGS items between the patient groups with high and low mean ratios of acyl-/total ghrelin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, a flavonoid in rikkunshito suppressed cisplatin-induced decreases in the plasma acylated ghrelin level and increased food intake mediated by 5-HT2B/2C receptors [16]. In general, rikkunshito is used to treat various gastrointestinal tract disorders such as functional dyspepsia (FD) [17,18], gastro-esophageal reflux [19,20], dyspeptic symptoms of post-gastrointestinal surgery [21,22], and chemotherapy-induced nausea [23]. In animal experiments, rikkunshito is reported to ameliorate gastric distension via a nitric oxide-mediated pathway, and it has also been shown to improve delayed gastric emptying [24].…”
Section: Introductionmentioning
confidence: 99%